Upregulation of antimicrobial peptide expression in slc26a3-/- mice with colonic dysbiosis and barrier defect. (31st December 2022) - Kini, Archana; Zhao, Bei; Basic, Marijana; Roy, Urmi; Iljazovic, Aida; Odak, Ivan; Ye, Zhenghao; Riederer, Brigitte; Di Stefano, Gabriella; Römermann, Dorothee; Koenecke, Christian; Bleich, André; et al.
ABSTRACT: Genetic defects in SLC26A3 (DRA), an intestinal Cl − /HCO3 − exchanger, result in congenital chloride diarrhea (CLD), marked by lifelong acidic diarrhea and a high risk of inflammatory bowel disease. Slc26a3 −/− mice serve as a model to understand the pathophysiology of CLD and search for treatment options. This study investigates the microbiota changes in slc26a3 −/− colon, the genotype-related causes for the observed microbiota alterations, its inflammatory potential, as well as the corresponding host responses. The luminal and the mucosa-adherent cecal and colonic microbiota of cohoused slc26a3 −/− and wt littermates were analyzed by 16S rRNA gene sequencing. Fecal microbiota transfer from cohoused slc26a3 −/− and wt littermates to germ-free wt mice was performed to analyze the stability and the inflammatory potential of the communities. The cecal and colonic luminal and mucosa-adherent microbiota of slc26a3 −/− mice was abnormal from an early age, with a loss of diversity, of short-chain fatty acid producers, and an increase of pathobionts. The transfer of slc26a3 −/− microbiota did not result in intestinal inflammation and the microbial diversity in the recipient mice normalized over time. A strong increase in the expression of Il22, Reg3β/γ, Relmβ, and other proteins with antimicrobial functions was observed in slc26a3 −/− colon from juvenile age, while the mucosal and systemic inflammatory signature was surprisingly mild. The dysbiotic microbiota, low mucosal pH, and mucus barrier defect in slc26a3 −/− colon are accompanied by a stark upregulation of the expression of a panel of antimicrobial proteins. This may explain the low inflammatory burden in the gut of these mice.